2008
DOI: 10.3382/ps.2008-00149
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feed Particle Size on the Performance, Energy Utilization, Digestive Tract Development, and Digesta Parameters of Broiler Starters Fed Wheat- and Corn-Based Diets

Abstract: The influence of particle size and grain type on the performance, AME(n), and on gross morphological and histological parameters of the various segments of the digestive tract of broilers fed wheat- or corn-based diets was investigated. The experimental design was a 2 x 2 factorial arrangement of treatments evaluating 2 particle sizes (fine and coarse) and 2 grain types (wheat and corn). The 2 particle sizes were achieved by grinding the whole grains in a hammer mill to pass through 1-mm and 7-mm screen sizes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 20 publications
10
83
1
Order By: Relevance
“…However, wet or dry milling of dried roots had little effect on the composition [48]. While composition is not affected, particle size is a key factor that affects feeding and performance in broiler chickens [49,50]. However, it is worthy to note that a high yield of starch does not necessarily mean the starch would have the desired quality for any specific application [51].…”
Section: Physical Processing Of Cassava For Poultry Feedingmentioning
confidence: 99%
“…However, wet or dry milling of dried roots had little effect on the composition [48]. While composition is not affected, particle size is a key factor that affects feeding and performance in broiler chickens [49,50]. However, it is worthy to note that a high yield of starch does not necessarily mean the starch would have the desired quality for any specific application [51].…”
Section: Physical Processing Of Cassava For Poultry Feedingmentioning
confidence: 99%
“…Similar differences between corn and wheat diets have been reported by Abdollahi et al (2013b) comparing mash and pelleted diets. In contrast, Amerah et al (2008) did not observe any difference in the relative weight of the gizzard at 21 d of age of broilers fed a corn or a wheat based diet, although the relative length (cm/kg BW) of the different segments of the GIT was shorter in birds fed wheat. Thomas and Ravindran (2008) reported similar relative weight of the GIT and the gizzard at 14 d of age in birds fed diets based on corn or wheat.…”
Section: Effects On Gastrointestinal Tract Developmentmentioning
confidence: 53%
“…The improvements observed for BW gain and FCR were consistent with the greater FI and the reduction in feed wastage detected. Amerah et al (2008) reported higher ADFI and poorer efficiency in broilers from 1 to 21 d of age fed pelleted diets, based on fine corn or wheat (1-mm screen), than in those fed diets based on coarse corn or wheat (7-mm screen). Fine particles are retained for less time in the gizzard than coarse particles (Abdollahi et al, 2013a).…”
Section: Effects On Poultry Performancementioning
confidence: 99%
See 2 more Smart Citations